Formulasi dan Uji Stabilitas Fisik Sediaan Foot Sanitizer Tropical Spray Ekstrak Etanol Daun Sirih (Piper betle L.) - Yuni Widiastuti Hayoto; Aulia Debby Pelu; Muhammad Azril Hardiman Mahulauw (Institut Nalanda, 2024)
Foot sanitizer spray is an inventory containing 70%-95% etanol. The content of the active materials is alcohol that has the highest strength of bacteria. One of the plants empirically utilized by society as antiseptic antismell of feet is betel leaves (Piper betle L.). This study aimed to identify the chemical content of betel leaf (Piper betle L.), made fomulation of Foot Sanitizer Spray supplies from betel leaf etanol extract (Piper betle L.), and conducted a test evaluation inventory foot sanitizer spray as well as doing irritation tests against the probandus.This type of research was experimental research. The method used for this study includes: preparation of materials, sample extration (betel leaf), design fomulation of supply Foot Sanitizer Spray i.e. using three varied formulations with a 10% FI comparison, 15% FII, and FIII 20%, preparation of foot Sanitizer Spray and formulation evaluation test (physical stability test includes shape, color, smell), pH test and irritation test. The results of the research show the supply of Foot Sanitizer Spray from the esktrak etanol betel leaf (Piper betle L.) by using the concentration comparison of betel leaf extract, mentiones as FI 10%, FII 15% and FIII 20% have good shape, color, smell stability up to the storage of the seventh day, the result of the pH measurement is 4 to the seventh day, according to the standard of the topical availability pH based on the pH of the skin which is 4-6.5.As well as not eliciting irritation effect on the probandus.